Surfactant-Assisted Synthesis of NiO-ZnO and NiO-CuO Nanocomposites for Enhanced Photocatalytic Degradation of Methylene Blue Under UV Light Irradiation - Weldekirstos, Hulugirgesh Degefu; Habtewold, Birtukan; Kabtamu, Daniel Manaye (Frontiers in Materials, 2022)
Photocatalytic process over semiconducting oxide surfaces has attracted worldwide attention as potentially efficient, environmentally friendly, and low-cost methods for wastewater treatment. This study presented a straightforward, inexpensive, and rapid route for synthesis of Nickel oxide (NiO) and its composites with Zinc oxide (NiO/ZnO) and copper oxide (NiO/CuO) nanoparticles through chemical precipitation method using capping agent- hexadecyltrimethylammonium bromide (CTAB) for photocatalytic degradation of methylene blue dye. The structure, morphology, and elemental constituents were characterized by X-ray diffraction, scanning electron microscopy, and energy dispersive X-ray spectroscopy. The energy band-gap of pure NiO, NiO-ZnO and NiO-CuO composites was evaluated with Tauc plot from absorption spectra and resulted as 3.00, 2.90 and 3.25 eV, respectively. The optimum parameters for all photocatalysts were: pH 8, Irradiation time 175 min, Catalyst amount 75 mg, and Dye concentration 7 mg/L. At these optimum parameters, the degradation efficiency of the prepared photocatalysts towards MB dye achieved was: 89.8% for NiO, 97% for NiO/ZnO, and 94.2% for NiO/CuO. The highest activity of the p-type/n-type (NiO/ZnO) nanocomposite for MB degradation is possibly due to electron – hole pair recombination inhibition by charge transfer processes. Therefore, semiconducting composite based nanocatalysts like NiO/ZnO with high photocatalytic activity are promising for future industrial applications to remove undesirable organic pollutants from the environment.